The Influence of Free Nutritious Food Program on Students' Learning Motivation At SMPN 1 Sungguminasa, Gowa Regency - Syamsidah, Syamsidah; Qur’ani, Besse; Burhanuddin, Izmi; Amir, Syarah Syam (Universitas Negeri Makassar, 2025)
Abstract. This study aims to analyze the effect of a free nutritious food program on the increase of students’ learning motivation at SMP Negeri 1 Sungguminasa, Gowa Regency. A quantitative approach was employed with a one-group pretest-posttest design. The study sample was 90 randomly selected students. Data were collected through a questionnaire to measure learning motivation before (pre-test) and after (post-test) the program. Descriptive analysis showed a significant increase in learning motivation. The average score of student motivation increased from 2.732 (category